Grass-microbial inter-domain ecological networks associated with alpine grassland productivity - Wang, Yingcheng; Dang, Ning; Feng, Kai; Wang, Junbang; Jin, Xin; Yao, Shiting; Wang, Linlin; Gu, Songsong; Zheng, Hua; Lu, Guangxin; Deng, Ye (Frontiers in Microbiology, 2023)
Associations between grasses and soil microorganisms can strongly influence plant diversity and community structures. However, the associations between grass productivity and soil microbes remain unclear. Here, we surveyed grass diversity and productivity, and sequenced soil archaea, bacteria and fungi by metabarcoding technology at 16 alpine grasslands. Using the Distance-decay relationship, Inter-Domain Ecological Network (IDEN), and Mantel tests, we investigated the microbial community changes of four types of grasslands: alpine swamp meadows, alpine meadows, alpine steppe, and temperate steppe, as well as the relationship between grass productivity, diversity and microbial diversity. We found grass productivity, diversity, and soil variables were positively or negatively correlated with α diversity of soil microorganisms, but these correlations varied with different microbial groups. Compared with grass diversity and soil variables, there was a positive correlation between grass productivity and archaea and bacteria α diversity. Meanwhile, all these microbial β-diversities were highly correlated with grass productivity, diversity, and soil variables, but grass productivity explained more strongly changes in microbial communities. The grass species formed complex and stable ecological networks with some bacterial, archaeal, and fungal species, and the grass-fungal ecological networks showed the highest robustness. Besides, the connectivity degrees of the grass-microbial network were significantly positively correlated with grass productivity and diversity, suggesting that the strength of grass-microbial associations would have a feedback effect on above-ground grass growth. These results suggest that grassland productivity has a strong interaction with soil microbial communities, and the positive links of the grass-microbe networks further prove that there is a strong interrelationship between above- and below-ground species in these alpine grasslands. The results are important for establishing the regulatory mechanisms between plants and microorganisms in alpine grassland ecosystems.